1971
DOI: 10.1159/000252189
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Evaluation of Skin Structures by Stereologic Methods

Abstract: A method is presented for the volumetric analysis of skin structures using simple point-counting principles of stereology. The anisotropic structure of skin requires particular attention in sampling microscopic fields for measurement. This method is applied to a preliminary study of skin specimens from male rats treated with parenteral testosterone; the volume of hair follicles was found to be significantly reduced to 1/3 of the control value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

1976
1976
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…This material was examined under a linear magnification of 28x . We counted the total number of spots representing the number of active se baceous follicles as well as the size of the spots by using an image analyzer MOP-Videoplan with the principles of morphometry [Weibel, 1963;Weibel et al, 1966;Sauter and Weibel, 1971]. In arbitrary units, the smallest surface of the spots was considered as one unit.…”
Section: Methodsmentioning
confidence: 99%
“…This material was examined under a linear magnification of 28x . We counted the total number of spots representing the number of active se baceous follicles as well as the size of the spots by using an image analyzer MOP-Videoplan with the principles of morphometry [Weibel, 1963;Weibel et al, 1966;Sauter and Weibel, 1971]. In arbitrary units, the smallest surface of the spots was considered as one unit.…”
Section: Methodsmentioning
confidence: 99%
“…Androgen‐dependent hair follicles secrete soluble factors in response to testosterone such as IGF‐1 that stimulate the growth of follicular epithelial cells 47 or inhibit the growth of complete hair follicles 48 . Other groups have reported on the secretion of stem cell factor 49,50 upon stimulation with testosterone. Whether this is of pathophysiological importance in AGA is notyet known.…”
Section: Androgen‐responsive Genesmentioning
confidence: 99%
“…Most stereological investigations have been performed at the ultrastructural level, where a considerable range of cytological parameters can be quantified. Only a few stereological studies have employed histological material (Sauter and Weibel, 1971;Dunnill and Whitehead, 1972;Underwood, 1972;Risdon, 1974;Risdon and Keeling, 1974;Gerstl, Wong and Yesner, 1976); this is probably due to the limited resolution of the light microscope and the difficulties that may be involved in identifying profile boundaries in histological sections of finite thickness. Some of these studies, however, have shown potential for diagnostic use.…”
Section: Pathological Implicationsmentioning
confidence: 99%